Third generation sexism in workplaces: Evidence from India. Issue 3 (3rd July 2018) - Goel, Sangeeta
ABSTRACT: Earlier literature indicates that, of late, crude biases against women in workplace or 'first generation bias' is giving way to more subtle, invisible 'second-generation bias.' Through this study, I found that not only did subtle forms of sexism exist, but the crudest possible forms continue to persist and impact the work environment adversely. A complex amalgam of 'old' and 'new' sexism is what I term 'third generation bias.' Using organizational ethnography, I gathered evidence of sexist attitudes in multiple forms, ranging from the crudest to the subtlest, which revealed the underlying and complex power dynamics in the workplace. I, therefore, made the case against assuming that because anti-sexual harassment policies are in place, crude sexist practices like overt sexual harassment are a thing of the past. I also suggested the use of technology and training for both men and women, besides deploying people with right attitudes to tackle the issue. Lastly, the study recommends that policy studies need to divert their attention from 'mere statistics' and focus on the behavioural dynamics of the organizations.